2022
DOI: 10.1002/cptc.202100253
|View full text |Cite
|
Sign up to set email alerts
|

External Magnetic Field Driven, Ambidextrous Circularly Polarized Electroluminescence from Organic Light Emitting Diodes Containing Racemic Cyclometalated Iridium(III) Complexes

Abstract: This work reports the development of external magnetic field (EMF) driven, ambidextrous, circularly polarized electroluminescence (CPEL) devices, by embedding racemic mixtures of phosphorescent organoiridium(III) emitters in the active emitting layer. Homoleptic tris‐cyclometalated Ir(III)(ppy)3 and heteroleptic bis‐cyclometalated Ir(III)(ppy)2(acac) (ppy=2‐phenylpyridinate, acac=acetylacetonate) were used as the representative organoiridium(III) compounds. Chiroptical inversion of CPEL was influenced by the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…As a new approach, we have been focusing on the magneto-optical effect on a luminophore in the excited state and previously reported that the application of an external magnetic field to organic light-emitting diodes (OLEDs) leads to the generation of circularly polarized electroluminescence (CPEL) [15][16][17]. As representative examples, we have developed magnetic circularly polarized OLED systems by incorporating optically inactive, racemic phosphorescent bis-and tris-cyclometalated iridium(III) complexes as emitting dopants [15]. Doping various iridium(III) luminophores into the emitting layer allowed us to obtain red-green-blue-yellow full-color, circularly polarized electroluminescent devices [16].…”
Section: Introductionmentioning
confidence: 99%
“…As a new approach, we have been focusing on the magneto-optical effect on a luminophore in the excited state and previously reported that the application of an external magnetic field to organic light-emitting diodes (OLEDs) leads to the generation of circularly polarized electroluminescence (CPEL) [15][16][17]. As representative examples, we have developed magnetic circularly polarized OLED systems by incorporating optically inactive, racemic phosphorescent bis-and tris-cyclometalated iridium(III) complexes as emitting dopants [15]. Doping various iridium(III) luminophores into the emitting layer allowed us to obtain red-green-blue-yellow full-color, circularly polarized electroluminescent devices [16].…”
Section: Introductionmentioning
confidence: 99%
“…One solution to this challenge is to utilize the magnetic circular dichroism (MCD) theory proposed by Riehl and Richardson (Riehl and Richardson, 1977;Ghidinelli et al, 2021) to induce CPL because MCPL can be viewed as the reverse process of MCD. According to this theory, as a versatile physical bias, external static magnetic fields can induce chiral spectral signals from both ground and photoexcited states in many achiral and racemic optically inactive organic, organometallic, and inorganic luminescent materials (Rikken and Raupach, 1997;Valiev et al, 2014;Knowles et al, 2015;Wu et al, 2017;Ivchenko, 2018;Ghidinelli et al, 2020;Imai, 2020;Imai, 2021;Kitahara et al, 2021;Zhang et al, 2021;Hara et al, 2022).…”
mentioning
confidence: 99%